2003
DOI: 10.1152/ajpcell.00149.2003
|View full text |Cite
|
Sign up to set email alerts
|

Some sweet and bitter tastants stimulate inhibitory pathway of adenylyl cyclase via melatonin and α2-adrenergic receptors in Xenopus laevis melanophores

Abstract: Zubare-Samuelov, Meirav, Irena Peri, Michael Tal, Mark Tarshish, Andrew I. Spielman, and Michael Naim. Some sweet and bitter tastants stimulate inhibitory pathway of adenylyl cyclase via melatonin and ␣ 2-adrenergic receptors in Xenopus laevis melanophores. Am J Physiol Cell Physiol 285: C1255-C1262, 2003. First published July 2, 2003 10.1152/ajpcell.00149.2003.-The sweeteners saccharin, D-tryptophan, and neohesperidin dihydrochalcone (NHD) and the bitter tastant cyclo(Leu-Trp) stimulated concentrationdepende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Also, along these non-TRPV1 receptor mechanisms, we note that amphipathic molecules have been shown to open a variety of initially closed ion channels and thus may open channels in TRCs (6,33). Finally, in Xenopus laevis melanophores, it has been shown that saccharin can activate the melatonin receptor, which also is expressed in rat circumvallate papille taste buds (57).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Also, along these non-TRPV1 receptor mechanisms, we note that amphipathic molecules have been shown to open a variety of initially closed ion channels and thus may open channels in TRCs (6,33). Finally, in Xenopus laevis melanophores, it has been shown that saccharin can activate the melatonin receptor, which also is expressed in rat circumvallate papille taste buds (57).…”
Section: Discussionmentioning
confidence: 83%
“…Initially, we consider how AS may affect the taste system via transduction pathways in TRCs. The elegant work of Naim and colleagues (40,57,58) provides a rationale for the lingering aftertaste of AS that does not require the activation of TRPV1 channels. They showed that AS, like saccharin, can diffuse across the plasma membrane of the TRCs and accumulate, at relatively high concentrations, in the cytoplasm where they may interact with and subsequently delay signal-termination components located downstream of the sweet or bitter responding GPCRs (depending on the concentration).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, such effects are plausible based on evidence that greater structural flexibility in CGRP proteins, which is required for ligand binding and allostery, is associated with greater thermal instability (Vihinen 1987;Yuan et al 2005). It is also not yet certain that hT2R receptors are the sole transduction pathway for bitter taste in humans (Zubare-Samuelov et al 2003;OliveiraMaia et al 2009). This remains an open question in part because cognate hT2R receptors have not been identified for several bitter substances that have been tested, including naringin (Meyerhof et al 2010).…”
Section: Effects Of Temperature On Initial Bitter Taste Intensitymentioning
confidence: 99%